ANALISIS HUBUNGAN ANTARA KOMITMEN KEORGANISASIAN DAN KINERJA PEGAWAI PUSKESMAS INPRES 7/87 PAYO SELINCAH JAMBI - Fitri S., Ajeng Sulistiya (Jurnal Dinamika Manajemen, 2023)
The study is titled :â€ Analisisi Relationship Between Organizational Commitment and Employee Performance Intruction Health Center 7/87 Payo Selincah Jambi â€œ. The purpose of this study was to determine the Relationship Between Organizational Commitment and Employee Performance in the Health Center 7/87 Payo Selincah Jambi. The method used in this research is descriptive analysis method is the method of data analysis the compare the implementation of the organization with the rules â€“ rules and based on existing the theories and practices of data displayed in the from of average. Presidential Health Center 7/87 Payo Selincah Jambi agile as a fungtional unit health care is center to the development of public health are engaged in health services. From the results of research and discussion of the study entitled â€œ Analysis of the relationship between organizational commitment and employee performance Instructuction Health Center 7/87 Payo Selincah Jambi the conclusion that these three aspects of organizational commitmen had the strongest relationship to the employee health center performance Intruction 7/87 Payo Selincah Jambi is a Affective Commitmment.